Perspektif Hukum Pidana dalam Penanggulangan Kejahatan Romance Scam : Analisis Peran Subdit V Siber Ditreskrimsus Polda Lampung - Khoirunnisa Khoirunnisa; Eko Raharjo; Fristia Berdian Tamza; Firganefi Firganefi (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
Cybercrime is increasing along with technological developments. The more people are connected to the internet, the more potential they have to experience crime in cyberspace. One of the cybercrimes is the crime of romance scam which is classified as an online fraud crime. The purpose of this study is to analyze the role of Sub-Directorate V Cyber Crime Directorate of Criminal Investigation in tackling romance scam crimes and their inhibiting factors. Using normative juridical and empirical juridical research methods, data were obtained through literature studies and field studies and analyzed by qualitative descriptive methods. Based on the results of the study, the Sub-Directorate V Cyber Crime Directorate of Criminal Investigation has never handled romance scam cases until the investigation due to a lack of evidence and other factors. Sub-Directorate V Cyber Crime Directorate of the Lampung Police has been active in various countermeasures with non-penal means such as conducting socialization and education to the public, cyber patrols, and digital forensic analysis. It is hoped that the public will be more careful in using social media, a healthy internet culture is needed and digital literacy is needed, and the government needs to revise laws and regulations regarding cybercrime.